2007
DOI: 10.1103/physrevb.76.125206
|View full text |Cite
|
Sign up to set email alerts
|

Character of states near the Fermi level in (Ga,Mn)As: Impurity to valence band crossover

Abstract: We discuss the character of states near the Fermi level in Mn-doped GaAs, as revealed by a survey of dc transport and optical studies over a wide range of Mn concentrations. A thermally activated valence-band contribution to dc transport, a midinfrared peak at energy ប Ϸ 200 meV in the ac conductivity, and the hot photoluminescence spectra indicate the presence of an impurity band in low-doped ͑Ӷ1% Mn͒ insulating GaAs:Mn materials. Consistent with the implications of this picture, both the impurity-band ioniza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 50 publications
(83 reference statements)
10
116
1
Order By: Relevance
“…Fermi level is pinned within the valence band for donorfree samples, or within the localized gap states of s-type for donor-rich samples and low Mn dopings -these samples are insulating and nonmagnetic. With the above findings, models for Curie temperature in dilute magnetic semiconductor (Ga,Mn)As, which assume an extended hole density function over the valence band 7,25,26 , are clearly justified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fermi level is pinned within the valence band for donorfree samples, or within the localized gap states of s-type for donor-rich samples and low Mn dopings -these samples are insulating and nonmagnetic. With the above findings, models for Curie temperature in dilute magnetic semiconductor (Ga,Mn)As, which assume an extended hole density function over the valence band 7,25,26 , are clearly justified.…”
Section: Discussionmentioning
confidence: 99%
“…As for the gap states at lower dopings, some publications imply that the origin of these states is from the valence band and their spin-polarization is of the d-type 26,28 . We have found that these states are spinunpolarized and of the s-type, and they are formed by a separation from the conduction band.…”
Section: Brief Summary Of Earlier Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…7,23 The description is based on the canonical Schrieffer-Wolff transformation of the Anderson Hamiltonian 24 which for ͑Ga,Mn͒As replaces hybridization of Mn d orbitals with As and Ga sp orbitals by an effective spin-spin interaction of ͑L =0; S =5/ 2͒ local moments with host valence-band states. This step proves essential to effectively separate the different AMR mechanisms ͑a,b,c͒, symbolized in Fig.…”
Section: Basic Model Of Amr In Metallic (Gamn)asmentioning
confidence: 99%
“…Mn Ga acceptors, with an impurity binding energy of 0.11 eV, 3,4 are more localized than shallower, hydrogeniclike acceptors in GaAs. This results in a higher critical carrier density for the metal-insulator transition (MIT) in Mn doped GaAs, of about 1×10 20 cm −3 , 5,6 as compared to the critical density for the shallow acceptors in GaAs, which is two orders of magnitude lower.…”
Section: Introductionmentioning
confidence: 99%